Nonnoble metal oxides for high‐performance Zn‐air batteries: Design strategies and future challenges. Issue 4 (29th April 2022) - Zheng, Qilong; Zhang, Yidan; Su, Chao; Zhao, Ling; Guo, Youmin
Abstract: Nowadays, the increasing demand for safe, clean, and renewable energies has inspired scientists to do massive research on rechargeable Zn‐air batteries (ZABs). Thanks to its inherent high theoretical energy density, ZABs have become one of the excellent candidates for the new generation of electric transportations and electrical energy storage systems. Nevertheless, the most significant technical obstacle to the commercialization of ZABs is the tardy oxygen reduction reaction and oxygen evolution reaction (ORR and OER) kinetics of the air electrode. Hence, the development of bifunctional electrocatalysts with advanced ORR/OER catalytic activity and long‐term stability is of great significance. Owing to the outstanding advantages of perovskite oxides, scientists have focused their attention on the perovskite‐based catalysts. And various strategies have been applied to strengthen their ORR/OER performance, including cation doping, surface structure optimization, nanostructure construction, and composite fabrication. This article concisely outlines the research progress of perovskite‐based oxides on ZABs applications. The basic principles of ZABs and the approach to increasing the OER/ORR activity of perovskite oxides as the air electrode of ZABs are illustrated. Finally, this review points out opportunities, possibilities, and future development direction of perovskite‐based air electrodes.